Effects of home visiting programmes on community-dwelling older adults with chronic multimorbidity: a scoping review - Anabel Chica-Pérez; Iria Dobarrio-Sanz; María Dolores Ruiz-Fernández; Matías Correa-Casado; Isabel María Fernández-Medina; José Manuel Hernández-Padilla (BMC, 2023)
Abstract Background Chronic ultimorbidity is the most frequent and serious health problem in older adults. Home visiting programmes could be a strategy with potential benefits. However, there are no scoping reviews to date that examine the effects of home visiting programmes on community-dwelling older adults with chronic multimorbidity. Objective To examine the effects of home visiting programmes on community-dwelling older adults with chronic multimorbidity. Methods A scoping review was carried out following PRISMA-ScR reporting guidelines. The search was conducted in six databases (PubMed/Medline, Cochrane, CINAHL, Web of Science, Scopus and EMBASE) between October 2021 and April 2022. Results Four RCTs with 560 patients were included. The visits were carried out by nurses, nursing students, volunteers, and other healthcare professionals. The interventions varied in the number of visits, frequency, duration of follow-up, and whether or not they were combined with other strategies such as telephone calls. Discrepancies were found in the effects of the interventions on quality of life, self-efficacy, self-rated health, and use and cost of health and social services. Conclusion This review shows that home visiting programmes could have potential benefits for older adults with chronic multimorbidity. However, its results have been inconclusive. There is a need for high quality studies involving a larger number of patients, in which home visits are the main intervention.